Supreme Court recognition of the FCC ancillary authority: Comparison with Brazilian courts interpretation on the doctrine of implied powers - Carmo, Rogerio Assis (Law, State and Telecommunications Review, 2013)
Purpose ”“ This update proposes the comparison between ancillary authority and implied power doctrine applied on Brazilian administrative agencies competences. Methodology/approach/design ”“ It describes the design of FCC’s ancillary jurisdiction based on US Supreme Court and Court of Appeals for the District of Columbia decisions. It also presents Brazilian doctrine and Federal Supreme Court justices’ opinions on the recognition of implied powers necessary to fulfill legal duties. Findings ”“ This study found confluence between those two theoretical sources ”“ ancillary authority and implied power doctrine ”“ towards the recognition of not directly expressed administrative agencies regulatory authority. Practical implications ”“ This update contributes to the recognition of Brazilian telecommunications regulatory agency’s powers which, although not expressly disposed, emerge as an imperative to fulfill responsibilities given directly by legal statutes. Originality/value ”“ This study presents the concept of ancillary authority current in the American tradition that, although not yet confirmed under Brazilian telecommunications law, it is commensurable to concepts already accepted by the Brazilian Supreme Court in accord with the implied power doctrine.